THE ELABORATION OF SACRED AND PROFANE IN FINE ART WORK ENTITLED "WHEN HANDS AND FEET ARE TALKING” - Zarkasi, Much. Sofwan; Suwasono, Bening Tri (Acintya, 2024)
The article "Sacred and Profane Elaboration in a Work of Art Titled When Hands and Feet Speak" by Much. Sofwan Zarkasi and Bening Tri Suwasono explores the intersection of sacred and profane elements in art, a convergence rarely seen in modern works that typically separate art and religion. This meeting of sacred and profane is grounded in Islamic prophetic values derived from Quranic knowledge. The authors argue that since the purpose of human life is to worship, and art is a part of human activity, art should also encompass the concept of worship. Thus, art becomes a blend of sacred and profane activities, presenting visual beauty and values that remind humans to protect the world from harm. The method used in creating "When Hands and Feet Speak" follows the stages of creation by L.H. Chapman: a) finding ideas, b) refining, developing, and solidifying initial ideas, and c) visualizing in the medium. This process is enhanced by adding d) the intention to work for worship at the beginning and including evaluation and gratitude at the end. The technique combines printmaking and collage to produce the final artwork. Keywords: Elaboration, Sacred, Profane, Fine Arts